PENGARUH MODAL SOSIAL TERHADAP KESEJAHTERAAN PENDUDUK PESISIR ROKAN HILIR RIAU INDONESIA - Firman Nugroho; Darwis AN; Trisla Warningsih; Lamun Bathara; Hazmi Arief (Jurnal Sosioteknologi, 2022)
This study aimed to analyze the effect of social capital on the welfare of the coastal population of Rokan Hilir Regency. This study used a survey method with a quantitative approach. Welfare indicators include income, family expenditure, health and access to health services, housing conditions and facilities, education, and access to transportation. Meanwhile, the indicators of social capital include network participation variables, reciprocal relations, trust, social norms, social values ​​and proactiveness. The results of this study showed that six variables of social capital had a positive influence on the increase in coastal people welfare. These variables contribute at the level of 64.0% in terms of welfare improvement. The network participation variable (PN) affects more effectively than other variables, where an increase of one unit of the network participation index (PN) will increase the welfare level index (Y) to 0.451. Furthermore, the reciprocity (RC) and proactive (PR) variables have an equal effect on welfare, where an increase of one unit will increase the welfare index (Y) by 0.120 - 0.124 units with a significant level of 0.1. Finally, the variables of trust (TR), norm (SN) and value (SV) have an equal effect on welfare (Y) of 0.9 - 0.112, meaning that if one or all the three variables increase by one unit index, the welfare (Y) will increase between 0.9 - 0.112 index units